Compensation of a hydraulic pipeline resonance by fluid–structure interaction. Issue 1 (2nd January 2018) - Mikota, Gudrun; Haas, Rainer; Lukachev, Evgeny
Abstract: For a pipeline between a valve block and a cylinder, the second hydraulic resonance is compensated by adding an appropriate mass in the most flexible part of the pipeline structure. The second maximum in the magnitude of measured pressure can thus be reduced to 65%. Frequency response functions between flow rate excitation and pressure as well as velocity response are calculated from a plane analytical model, including junction coupling. Results are validated against measurements in configurations with and without additional mass and with different layers of rubber in between. Calculated pressure responses clearly reproduce the measured compensation effect, and the model also provides a rough approximation of structural vibrations.